Health shocks in Sub-Saharan Africa: Are the poor and uninsured households more vulnerable? - Esso-Hanam Atake (Health Economics Review, 2018)
Background: In developing countries, health shock is one of the most common idiosyncratic income shock and the main reason why households fall into poverty. Empirical research has shown that in these countries, households are unable to access formal insurance markets in order to insure their consumption against health shocks. Thus, in this study, are the poor and uninsured households more vulnerable from health shocks? We investigate the factors that lead to welfare loss from health shocks, and how to break the vulnerability from health shocks in three Sub-Saharan Africa (SSA) countries, namely, Burkina Faso, Niger and Togo. Methods: This study focusses on 1597 households in Burkina Faso, 1342 households in Niger and 930 households in Togo. A three-step Feasible Generalized Least Squares (FGLS) method was used to estimate vulnerability to poverty and to model the effects of health shocks on vulnerability to poverty. Results: The estimates of vulnerability show that about 39.04%, 33.69%, and 69.03% of households are vulnerable to poverty, in Burkina Faso, Niger, and Togo respectively. Both interaction variables, 'health shocks and wealth' and 'health shocks and access to health insurance' had a significant negative effect on reducing household's vulnerability to poverty. Poverty is the leading cause of economic loss from health shocks as the poorer cannot afford the purchase of sufficient quantities of quality food, preventive and curative health care, and education. We found that lack of health insurance coverage had a significant effect by increasing the incidence of welfare loss from health shocks. Moreover, household size, type of health care used, gender, education and age of the head of the household as well as the characteristics of housing affect vulnerability to poverty. Conclusion: Our findings suggest that for the poor households, reduction of user fees of health care at the point of service or expansion of health insurance could mitigate vulnerability to poverty. Other challenges-birth control policy, adequate sanitation facilities and a universal basic education program-need to be addressed in order to reduce significantly the effects of health shocks on vulnerability to poverty in SSA.
Keywords: 330; Vulnerability to poverty; Health shocks; Health insurance; Poverty; Fertility; Sanitation; Education; Sub-Saharan Africa